Джерела формування мовної особистості Агатангела Кримського - Данилюк, Н.; Рогач, О. (Культура слова, 2021)
Статтю присвячено джерелам формування мовної особистості майбутнього видатного вченого, письменника, перекладача, поліглота Агатангела Кримського. Здійснений аналіз
комунікативно-географічного та епістолярно-дискурсивного
простору засвідчує, що становлення його мовної особистості відбулося в дитячі та юнацькі роки. Зауважено, що її риси
визначили походження (генетичні корені, вчительська сім’я,
унікальні здібності), багатомовні й багатокультурні місця проживання і навчання (Володимир-Волинський (тепер –
Володимир), Звенигородка, Острог, Київ, Москва, Бейрут),
гідні наслідування Вчителі (насамперед П. Житецький та
В. Міллер), спілкування з видатними сучасниками (І. Франком,
Б. Грінченком, О. Огоновським, М. Павликом, Лесею Українкою та ін.). The article is devoted to the sources of the formation of a linguistic
persona of the future famous scholar, writer, translator, and polyglot –
Ahatanhel Krymskyi. In the article there has been conducted
an analysis of the communicative geographical and epistolary
discursive area of A. Krymskyi at the times of his childhood and
adolescence. These periods of his life we consider the decisive
ones for his linguistic individualization and the definition of the
parameters of a linguistic persona. The linguistic persona’s features
were caused by the origin of A. Krymskyi (the Crimean Tartar roots,
an intelligent family of a teacher of history and geography and a
Polish Lithuanian noble woman), and his unique abilities (the boy
learned to read at the age of 3 and a half, had a phenomenal memory,
and an analytical brain). A great role was played by the multilingual
and multicultural places of dwelling and studying, namely the
following towns and cities: Volodymyr Volynskyi, Zvenyhorodka,
Ostroh, Kyiv (such languages as Ukrainian, Russian, Polish, and
Yiddish were spoken there and different ethnic cultures cooperated),
Moscow (A. Krymskyi was surrounded by the Russian, Ukrainian,
and other languages; a Ukrainian community was actively working),
Beirut (in the city, the Arabic, French, Russian, and other languages
were spoken; there was a unique environment of Eastern/Oriental
cultures). The formation of a polyglot was favoured by the study
of classical languages, Western European, Slavonic and Eastern /
Oriental languages at the secondary and higher educational
institutions. The evolution of scientific abilities of the specialist in
the Ukrainian, Slavonic and Oriental studies was supported by the
highly professional teachers (first of all Pavlo Zhytetskyi in Kyiv
and Vsevolod Miller, Oleksii Veselovskyi, Ihnatii Krachkovskyi in
Moscow). The communication with famous people (Ivan Franko,
Borys Hrinchenko, Omelian Ohonovskyi, Mykhailo Pavlyk,
Lesia Ukrainka and others) intensified the Ukrainian vector of the
linguistic persona of A. Krymskyi. Creative possibilities of the
linguopersona-writer and translator are reflected in his literary and
translation heritage (the collection of poems “Palm branches” (1901,
1908), “The Stories of Beirut” (1906), the novel “Andrii Lahovskyi”
(1905, a full version was published in 1972), translations of the
poetry by Hafez, Omar Khayyam, Saadi, Ferdowsi, Turkish folk
songs and others into Ukrainian and Russian.